Generation of Surface Plasmon Resonance and Lossy Mode Resonance by thermal treatment of ITO thin-films. (June 2015) - Del Villar, I.; Zamarreño, C.R.; Hernaez, M.; Sanchez, P.; Arregui, F.J.; Matias, I.R.
Abstract: Silicon wafers coated with Indium Tin Oxide (ITO) by application of sputtering technique have been characterized after different post-annealing techniques, showing that this last factor is critical for the quality of the thin-film and for the creation and tuning of both surface plasmon resonances and lossy mode resonances. By adequate selection of the ITO thin-film thickness both resonances can be tracked in the same spectrum, which can be used in sensor and optical communications fields. Highlights: Study of Surface Plasmon and Lossy Mode Resonance obtained with an ITO thin-film. ITO is characterized with SEM, XRD, AFM, contact angle, conductivity, and ellipsometry. Influence of post-annealing on the position of resonances in the optical spectrum.